Genetic parameters for tick count and udder health in commercial and indigenous ewes in South Africa - Cloete, S.W.P.; Cloete, J.J.E.; Scholtz, A.J. (Veterinary parasitology, 2016)
•Breed affected tick counts on three specific body sites as well as overall tick count.•An indigenous unimproved fat-tail breed had generally lower tick counts and udder health scores than two commercial breeds.•Ovine tick counts in ewes were heritable and genetically related to udder health.•Ewes with heavier mating weight also had higher tick counts at specific body sites.•Tick count was unrelated to reproduction in ewes. The genetics of tick infestation in sheep need study, as host resistance often forms part of integrated pest control programs. Repeated udder health scores, site-specific tick count, mating weight and reproduction records (N=879–1204) were recorded annually from 2010 to 2015 on ewes of the indigenous Namaqua Afrikaner (NA) fat-tailed breed, as well as the commercial Dorper and SA Mutton Merino (SAMM) breeds. Udders were scored subjectively on a 1–5 scale (1 – udder intact and 5 – udder damaged severely) and ticks were counted on three locations. The body sites counted were the head and thoracic limb (HTLTC), udder-pelvic limb (UPLTC) and perineum-breech-tail (PBTTC). These counts were also totaled for a total tick count (TTC). Reproduction traits were number of lambs weaned per ewe lambed and total weight of lamb weaned per ewe lambed. Udder health scores of NA ewes were lower than those of Dorpers, which in turn had lower scores than SAMM ewes. NA ewes had lower values for HTLTC, UPLTC and TTC than the commercial breeds, but higher values for PBTTC than Dorpers. Heritability estimates amounted to 0.26±0.04 for HTLTC, 0.53±0.04 for UPLTC, 0.07±0.06 for PBTTC, 0.44±0.06 for TTC and 0.61±0.03 for udder health score. Animal permanent environment also affected PBTTC (0.14±0.07). Significant genetic correlations were found between the HTLTC and UPLTC (0.47±0.10), UPLTC and udder health score (0.52±0.07), HTLTC and UPLTC (0.24±0.11) as well as UPLTC and PBTTC (−0.44±0.11). Heavier ewes had higher UPLTC (0.38±0.09), TTC (0.33±0.09) and impaired udder health (0.21±0.08). Udder health scores and tick counts at all sites were not related to reproduction traits. The indigenous NA breed outperformed the commercial breeds with lower values for HTLTC, UPLTC, TTC and a better udder health score. Mechanisms contributing to the better performance of the NA breed under pastoral conditions and the scope for selection for tick tolerance within breeds should be studied further.